Diseño de Procedimientos Técnicos como parte de un Sistema de Gestión de Calidad en Ensayos de Laboratorio - Fernández-Cerdas, Sergio (Instituto Tecnológico de Costa Rica, 2007)
The present directed professional practice is focused in the implementation of the applied technical procedures to two tests of laboratory. These procedures will be part of the System of management of quality of the company Ingeniería Técnica de Pavimentos S.A, the system is under the standards established by the norm INTE:ISO/IEC 17025:2005, which defines the competition of the laboratories and represents a fundamental tool for credit procedures of management and technicians before organizations whose competition is in the accreditation of these procedures; in these case the Costa Rican Organization of Accreditation. The development of the present objective has been raised following some programmed stages in coherent and ordered form. Because of it, the efficient knowledge of the norm, the establishment of the technician’s procedures associated to the technical documentation to elaborate, and the putting in practice of this last one, translated in the evaluation of the personal performance, will dictate the final result of the project and the company interests. All the previous one will be applied to the soils tests: Limits of Atterberg and Laboratory Compaction Characteristics of Soils (Standard and Modified Effort).
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción; 2007.
Keywords: Gestión de calidad; Norma; Acreditación; Procedimientos técnicos; Evaluación del desempeño